Understanding and Managing the Complexity of Healthcare - William B. Rouse, Nicoleta Serban (The MIT Press, 2014)
Breakthroughs in medical science along with innovations in clinical practices and related technologies offer enormous opportunities for impressive improvements in the health and well-being of society. Returns on investments in these endeavors have the potential to be substantial, sustainable, and broadly beneficial. However, we will not realize the greatest returns with our current fragmented system of healthcare delivery (Reid et al., 2005; Rouse & Cortese, 2010). Many see a need to engineer or design a system that can provide high quality, affordable healthcare for everyone. Engineering healthcare delivery will require that the current nondesigned enterprise be substantially transformed (Rouse, 2006a). This book is intended to be an important enabler of such fundamental change by providing and illustrating concepts, principles, models, and methods for understanding and improving the efficiency, effectiveness, and equity of healthcare delivery. This chapter proceeds as follows. We first discuss the nature of the problems associated with the current healthcare delivery system in the United States. This includes the forces driving needs for change, the types of issues that need to be addressed, and the complexity of these issues. We then address the objectives that transformation should be designed to achieve in terms of high-value healthcare, including definitions of value, how it is delivered, and the roles of information and incentives in providing value. We next consider alternative approaches to solving healthcare delivery problems, contrasting bottom-up and top-down approaches and the use of quantitative approaches to explore a wide range of solutions.